Construction of a Dynamic Normative Model of the Stock Valuation Rating - A. S. Tonkikh; S. A. Tonkikh; E. Yu. Maslova (Финансы: теория и практика, 2022)
Ratings are widely used in stock analysis, as they increase information transparency, simplify the assessment and investment decision-making in the stock markets, and increase their effectiveness. However, the use of ratings is constrained by subjective factors, which necessitates replacing expert assessments with objective characteristics. The aim of the study is to develop a stock valuation rating model, which allows obtaining additional information about the qualitative characteristics of shares in relation to existing rating methods, ensuring the transparency of the rating methodology and limiting the influence of subjectivity, affiliation and bias of an expert analyst. On the basis of the method of dynamic standard, a rating score is constructed, which expresses the measure of the proximity of the normative and actual order of the growth rates of indicators characterizing the investment attractiveness of stocks. When choosing current indicators for inclusion in the rating, the principle of their dynamic co-subordination (normative ordering by growth rates) proposed by I.M. Syroezhin and successfully used in the analysis of economic situations has been applied. The authors have built a share valuation rating model, which is a system of inequalities for the growth rates of six indicators (reference aggregated indicator — benchmark): the market price of a share, the size of the dividend per share, the company’s net profit, revenue, equity and the number of shares in circulation. One of the advantages of the developed model is its universality: it is applicable to any industry, any market, and any accounting system. The model will make it possible to address the problems of expert subjectivism, the use of projected values and the availability of initial information (indicators of official reporting). The authors note the limitation of the model — it is not applicable to the valuation of early-stage companies. The model has been tested by compiling ratings of common stocks from the MICEX index10 for one-year and five-year periods. A comparative analysis of the ratings showed that a higher rating of stocks is observed in the long term. This also determines the applicability of the developed model as a stock analysis tool for long-term fundamental investments.